Circumsporozoite Protein of Plasmodium berghei- and George Baker Virus A-Derived Peptides Trigger Efficient Cell Internalization of Bioconjugates and Functionalized Poly(ethylene glycol)-b-poly(benzyl malate)-Based Nanoparticles in Human Hepatoma Cells - Elise Vène; Kathleen Jarnouen; Catherine Ribault; Manuel Vlach; Yann Verres; Mickaël Bourgeois; Nicolas Lepareur; Sandrine Cammas-Marion; Pascal Loyer (MDPI AG, 2022)
In order to identify the peptides, selected from the literature, that exhibit the strongest tropism towards human hepatoma cells, cell uptake assays were performed using biotinylated synthetic peptides bound to fluorescent streptavidin or engrafted onto nanoparticles (NPs), prepared from biotin-poly(ethylene glycol)-block-poly(benzyl malate) (Biot-PEG-b-PMLABe) via streptavidin bridging. Two peptides, derived from the circumsporozoite protein of Plasmodium berghei- (CPB) and George Baker (GB) Virus A (GBVA10-9), strongly enhanced the endocytosis of both streptavidin conjugates and NPs in hepatoma cells, compared to primary human hepatocytes and non-hepatic cells. Unexpectedly, the uptake of CPB- and GBVA10-9 functionalized PEG-b-PMLABe-based NPs by hepatoma cells involved, at least in part, the peptide binding to apolipoproteins, which would promote NP's interactions with cell membrane receptors of HDL particles. In addition, CPB and GBVA10-9 peptide-streptavidin conjugates favored the uptake by hepatoma cells over that of the human macrophages, known to strongly internalize nanoparticles by phagocytosis. These two peptides are promising candidate ligands for targeting hepatocellular carcinomas.